Sembrar Derechos. Reconfiguración del trabajador rural como sujeto de derecho, en los procesos de integración regional y universal - Daniela Verónica Sánchez Enrique (Universidad Hemisferios, 2014)
This paper analyzes the reform of rural labor in Argentina, from the theoretical debate linked to the reconfiguration of the worker as a subject of universal rights and the transformation of demos, opposite the supranational rules generated by the processes of regional integration and globalization.The aim of this study is to analyze the impact of this process, rules and institutionally by the degree of incorporation of international human rights standards in the national legislation related to the new regime of Argentine agricultural work.The structure of this analysis contains three sections. In the first, the theoretical debate on the transformation of citizenship, caused by the tension between national legislation and international rights, to rethink the extent influences the transformation of the legal status of the worker, the subject develops subject to national law to regional and universal right. The second will make a brief analysis of some supranational law which manifests the internationalization of the rights of workers. Finally, we discuss the strategic points of the last reform of the Argentine rural work, trying to analyze the main changes. The selected for the development of this proposed methodology consists of theoretical analysis of the transformation of demos and regulations for the new regime of Argentine farm work (National Law 26,727), which will be supplemented by referring to bodies of Latin American regional integration and International Treaties on Human Rights, specifically on Economic, Social and Cultural Rights (ESCR).